2014
DOI: 10.1073/pnas.1414053111
|View full text |Cite
|
Sign up to set email alerts
|

Young capillary vessels rejuvenate aged pancreatic islets

Abstract: Pancreatic islets secrete hormones that play a key role in regulating blood glucose levels (glycemia). Age-dependent impairment of islet function and concomitant dysregulation of glycemia are major health threats in aged populations. However, the major causes of the age-dependent decline of islet function are still disputed. Here we demonstrate that aging of pancreatic islets in mice and humans is notably associated with inflammation and fibrosis of islet blood vessels but does not affect glucose sensing and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(129 citation statements)
references
References 49 publications
7
116
0
Order By: Relevance
“…7(c)). This percentage of vascularization is in the range of what was observed in islets in situ and is comparable to the vessel density measured by Almaça et al [7] in ACE islets after an intravenous injection of fluorescent labeled dextran.…”
Section: Islet Imaging Inside the Anterior Chamber Of The Eyesupporting
confidence: 89%
See 1 more Smart Citation
“…7(c)). This percentage of vascularization is in the range of what was observed in islets in situ and is comparable to the vessel density measured by Almaça et al [7] in ACE islets after an intravenous injection of fluorescent labeled dextran.…”
Section: Islet Imaging Inside the Anterior Chamber Of The Eyesupporting
confidence: 89%
“…Using functional optical coherence imaging (FOCI), we found that there is a strong correlation between the increasing inflammation of the islets and the density of their vascular network [6]. In addition, there are indications that the glucose intolerance observed in aged mice is due to a vascular impairment rather than β-cell defect [7]. The deep localization of these islets inside the pancreas in the abdominal cavity and their heterogeneous distribution throughout this organ renders imaging their vascularization challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Mice have also been used to study natural processes such as aging (Demetrius, 2006; Vanhooren and Libert, 2013). Our recent findings have shown that aged mice have pancreatic islets with hallmarks consistent with human islets from aged individuals (Almaca et al, 2014). This further supported the notion that the human islets in our mouse model are likely to be exposed to a systemic aging process during a prolonged liraglutide treatment of ≥250 days as in situ islets in the human pancreas during long-term multi-year use of incretin mimetic therapy (Flurkey et al, 2007; Jucker et al, 1994).…”
Section: Resultsmentioning
confidence: 88%
“…The key to prevention or reversal of diabetes may rest in the recently emphasized role of endothelium in beta-cell differentiation and maturation in vitro [52,53] . In addition, it has been suggested that EC pathology can lead to islet dysfunction suggesting that ECs are essential to maintain islet function in adults [97] .…”
Section: Talavera-adame D Et Al Endothelium Role In Pancreas Organomentioning
confidence: 99%